Extraskeletal mesenchymal chondrosarcoma at unusual location involving spleen and kidney with review of literature - Krushna Chandra Pani; Mahima Yadav; P Valli Priyaa; Niraj Kumari (Wolters Kluwer Medknow Publications, 2017)
Mesenchymal chondrosarcoma (MC) is a rare malignant neoplasm bearing characteristic dimorphic pattern histologically. We describe two rare cases of primary MC involving two different visceral organs (1) a 24-year-old man with solid renal mass and, (2) a 42-year-old man with cystic splenic mass. The histological and immunophenotypical features of both lesions were classical of MC. Although this lesion is uncommon in visceral organs, the possibility of this rare entity must be kept in differential diagnosis with compatible morphology.